GENERAL ELECTION FOR WELFARE - Kartini, Murtiningsih (Cirebon International Conference on Education and Economics Proceeding, 2024)
General elections or Pemilu are a form of legitimate means of transitioning a regime or power. The meaning of an election is so important, because of several things that underlie it. Among them are elections which are carried out directly, publicly, freely, secretly, honestly and fairly by the community directly, which is also a form of implementing democracy. Elections as an exercise of democracy. Elections also serve as a means of realizing democracy. Leadership elections occur at the central level, where state leaders are elected, as well as at the regional level, where governors are chosen and deputy governor, as well as at the district level electing the regent and deputy regent or mayor and deputy mayor. These prospective leaders will bring a vision and mission in their election which will later become a central or regional medium-term development program outlined in the form of a medium-term development plan document or text, which will be implemented over a five-year period during the period of exercising the powers of the elected leaders. This medium-term development plan must align with central and regional government programs to support community welfare development, reflecting the essence of a welfare state. Achieving a welfare state is one of the objectives of the Unitary State of the Republic of Indonesia. This paper uses a qualitative method that processes secondary data into descriptive analysis. This normative juridical research does not process a formula of numbers or statistics.